2019
DOI: 10.3389/fneur.2019.00174
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Site Transcranial Magnetic Stimulation for the Treatment of Parkinson's Disease

Abstract: Abnormal oscillatory activity in the subthalamic nucleus (STN) may be relevant for motor symptoms in Parkinson's disease (PD). Apart from deep brain stimulation, transcranial magnetic stimulation (TMS) may be suitable for altering these oscillations. We speculated that TMS to different cortical areas (primary motor cortex, M1, and dorsal premotor cortex, PMd) may activate neuronal subpopulations within the STN via corticofugal neurons projecting directly to the nucleus. We hypothesized that PD symptoms can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
(68 reference statements)
1
16
0
Order By: Relevance
“…Finally, Fricke and co-workers [75] hypothesised that PD symptoms could be ameliorated by a lasting decoupling of subthalamic nucleus neurons by associative dual-site rTMS (1 Hz) employed to the primary motor cortex and dorsal premotor cortex. To this aim, 20 PD patients were treated in a blinded, placebo-controlled cross-over design.…”
Section: Transcranial Magnetic Stimulation-tmsmentioning
confidence: 99%
“…Finally, Fricke and co-workers [75] hypothesised that PD symptoms could be ameliorated by a lasting decoupling of subthalamic nucleus neurons by associative dual-site rTMS (1 Hz) employed to the primary motor cortex and dorsal premotor cortex. To this aim, 20 PD patients were treated in a blinded, placebo-controlled cross-over design.…”
Section: Transcranial Magnetic Stimulation-tmsmentioning
confidence: 99%
“…Supplementary Table 1 shows characteristics of 28 finally selected studies. Among these studies, 25 studies [ 10 14 , 18 37 ] investigated the therapeutic effect of rTMS on motor in PD (including 409 patients given rTMS and 378 patients given sham stimulation). In the 25 studies, 14 studies were with crossover design, 11 studies were with randomized controlled design.…”
Section: Resultsmentioning
confidence: 99%
“…A novel protocol known as associative dual-site rTMS was implemented by Fricke et al, who hypothesized that simultaneous targeting of the dorsal premotor cortex and the M1 in a coordinated fashion might lead to decoupling of pathogenic oscillatory tremor activity (44). However, the study found no clinical improvements, suggesting that the optimal target site for PD tremor is still not clear (44). Based on the data from pathophysiological studies, it is reasonable to postulate that the rest and postural tremors are likely amenable to different stimulation sites.…”
Section: Therapeutic Use Of Rtmsmentioning
confidence: 99%
“…There is high variability in the rTMS paradigms and study designs used to investigate tremor syndromes, including differences in sham application, washout periods in crossover designs, target location, number of pulses, number of stimulation sessions, and duration of the stimulation in total. Many studies implemented only a single stimulation session (26,28,36,37,39,43,44,51,52,64,73), whereas other studies included multiple sessions ranging anywhere from 5 consecutive days to 15 stimulation days (38, 40-42, 47, 49, 50), or more unique protocols in which 5 consecutive days of stimulation are followed with a weekly session of stimulation for 3 weeks (53). The number of stimulation sessions may play a role in the duration of benefit, and thus it is critical to not only assess benefit following stimulation but also to assess how long that benefit lasts.…”
Section: Current Limitationsmentioning
confidence: 99%
See 1 more Smart Citation